Aspects on hereditary gastric cancer - Johanna Samola Winnberg (2025)
Gastric cancer has a poor prognosis, as it is often diagnosed at an advanced stage. Identifying individuals at high risk is essential in order to offer surveillance, early treatment or preventive measures, including prophylactic gastrectomy.Familial clustering of gastric cancer is observed in approximately one in ten cases, and hereditary gastric cancer with well-known genetic susceptibility accounts for around three percent of all gastric cancer cases, including Hereditary Diffuse Gastric Cancer (HDGC), Gastric Adenocarcinoma and Proximal Polyposis of the Stomach (GAPPS) and Familial Intestinal Gastric Cancer (FIGC). The risk of gastric cancer is also elevated in several other hereditary cancer syndromes, such as Lynch syndrome (disease-causing variants in one of the DNA mismatch repair genes), Li-Fraumeni syndrome (TP53), Familial Adenomatous Polyposis (APC), Peutz-Jeghers syndrome (STK11), MUTYH-associated polyposis, Juvenile Polyposis (SMAD4 or BMPR1A) and Hereditary Breast or Ovarian Cancer syndrome (BRCA1 or BRCA2). Yet, many families do not carry any recognised genetic cause.Over the past few decades, it has become clear that cancer is a disease with complex traits. Instead of focusing entirely on high-penetrance, single-gene variants, many current studies use multi-genic models to investigate associations between single variants or combinations of them, called haplotypes, across the genome, as seen in Genome Wide Association Studies (GWAS). Several GWAS on cancer have been carried out over the past decades, and many candidate regions (loci) and risk alleles have been associated with gastric cancer. However, few of these suggested variants are functional, and further studies are required to explore their biology. Lately, there has been an increased focus on loci that predispose individuals to more than one type of cancer, reflecting pleiotropy. Both pleiotropic and cancer-specific loci identified through GWAS have considerably expanded the list of genes influencing cancer risk. Nevertheless, it remains challenging to fully translate the results from GWAS into clinical practice, particularly in terms of prevention programmes or potential therapeutic targets.The overall aim of this thesis was to examine different aspects on hereditary gastric cancer, explore associations between gastric cancer and other malignancies, and investigate potential shared genetic predisposing factors for these tumours.In Paper I, a retrospective cohort study was conducted including 107 individuals previously diagnosed with gastric cancer. Cancer cases in close family members were recorded. The proportions of different cancer types among first- and second-degree relatives of the included patients were compared to those in the general Swedish population. The main finding was that both uterine cancer and gastric cancer were overrepresented compared to the reference population.Equivalent to Paper I, Paper II investigated cancer occurrences among close relatives of gastric cancer patients, but this time in a prospective setting. A total of 134 patients with newly diagnosed gastric cancer were included. The relative occurrence of different cancer types among first- and second-degree relatives was estimated and compared to the general Swedish population. Similar to Paper I, the relative occurrence of gastric cancer was higher than in the reference population. Among first-degree relatives, cancer of the small intestine was more common, while among second-degree relatives, the relative occurrence of both cervical cancer and bone cancer was higher than in the reference population. A lower relative occurrence was observed for prostate cancer and urinary tract cancer among both first- and second-degree relatives.In Paper III, a GWAS was conducted, consisting of 685 colorectal cancer cases, whose relatives had gastric and/or prostate cancer, and 4780 healthy controls from the Swedish Twin Registry. A sliding window haplotype analysis was undertaken using a logistic regression model. Candidate loci on ten chromosomal regions were suggested, most of which included protein-coding genes previously shown to be involved in cancer. Sequencing of DNA was then carried out on colorectal cancer patients with gastric and/or prostate cancer among their close relatives to search for candidate variants within these haplotype loci. Finally, the suggested candidate variants were investigated in a case-control study of colorectal cancer cases and healthy controls. Although no statistically significant results were noted in the final association study, the paper demonstrated proof of principle strategy to identify risk variants found by haplotype GWAS.Analogous to Paper III, in Paper IV a GWAS was undertaken with the same 685 cases, but with different controls. A total of 1642 controls, consisting of spouses of the cases and healthy blood donors from the same geographical region as the cases, were selected. Similar to Paper III, a sliding window haplotype analysis was conducted using a logistic regression model. The ten candidate loci identified in Paper III were replicated in the analysis, and 50 novel candidate loci were suggested, two of which were the same as in Paper III. DNA sequencing and a subsequent case-control study were carried out in the same manner and with the same cases and controls as in Paper III. One variant on locus 10q11.21 reached statistical significance. Further studies are required to determine the actual risk associated with the suggested loci.List of scientific papersI. Increased risk for uterine cancer among first-degree relatives to Swedish gastric cancer patients Samola Winnberg J, Rudd E, Keränen A, Lagerstedt-Robinson K, Lindblom A, Nilsson M, Lindblad M and Sjödahl K. Hereditary Cancer in Clinical Practice. 2020;18:12. https://doi.org/10.1186/s13053-020-00145-yII. Cancer among first- and second-degree relatives to Swedish patients diagnosed with gastric cancer Samola Winnberg J, Nilsson M, E. Vossen L, Lindblom A and Lindblad M. [Manuscript]III. A genome-wide association study in Swedish colorectal cancer patients with gastric- and prostate cancer in relatives Samola Winnberg J, Vermani L, Liu W, Soller V, Thutkawkorapin J, Lindblad M and Lindblom A. Hereditary Cancer in Clinical Practice. 2024;22(1):25. https://doi.org/10.1186/s13053-024-00299-zIV. A haplotype GWAS in syndromic familial colorectal cancer Vermani L, Samola Winnberg J, Liu W, Soller V, Sjödin T, Lindblad M and Lindblom A. International Journal of Molecular Sciences. 2025;26(2). https://doi.org/10.3390/ijms26020817